The effect of coupled inquiry-5E in enhancing the understanding of Meiosis concept - Nooraida Yakob; Kelvineh Kaliun; Ahmad Muslihin Ahmad; Rabiatul-Adawiah Ahmad Rashid; Amelia Abdullah (International Journal of Evaluation and Research in Education (IJERE), 2020)
The purpose of this study is to investigate the effectiveness of coupled inquiry-5E approach on the understanding of meiosis concept among pre-service teachers. The research design of this study is one-group design with a pre-test -post-test-delayed post-test. A total of 31 pre-service teachers from one public university involved in this study. An instrument, Meoisis Conceptual Test with 19 items was used. Data was analysed using One Way Repeated Measure ANOVA. The result showed that there is a statistically significant effect for time, Wilks’ Lambda =.80, F (2,29) = 3.65, p<.05, multivariate eta squared = .20. From the analysis, it can be concluded that there is a statistically significant effect for time. Thus, this finding showed that couple inquiry learning approach has an effect on enhancing meiosis understanding among pre-service teachers. From this study, it is suggested that couple inquiry learning approach is a good method to be used in learning abstract concept such as meiosis.